Future Prospects in Balanced Scorecard Research: Sustainability Perspective - Mehtap Aldogan Eklund (Universitas Pasundan, 2020)
This paper reviews the state of the research on a balanced scorecard (BSC) and sustainability balanced scorecard (SBSC) from 1990 to 2020. It aims to address the research question,